A 3D geological static field model of the Krafla geothermal area; constructing a workflow for the Pico Alto geothermal area - Unnur Þorsteinsdóttir 1992- (2017)
Compiling and summarising multidisciplinary results from geothermal areas often proves to be a complicated and challenging task. In such tasks, 3D models facilitate data comparison and enable a better understanding of the systems involved, resulting in a better and risk mitigated well targeting processes. This project involves 3D modelling of a geothermal field that has been exploited for years. The Krafla geothermal field is located in NE-Iceland and has a long history of research and exploitation. Here, the Krafla geological static model has been updated using research data that have not been implemented to the model before. These include recently acquired seismic data (location of quakes and tomography), 3D resistivity model, aero-magnetic data and Bouguer and Free-air gravity maps. Borehole data (cuttings analyses and geophysical logs), which have not been available in digital format before, have been included. Furthermore, datasets were compared and cross-correlated through deep structure sub-surface analysis. Lessons learned throughout the construction of the Krafla model resulted in a proposed workflow which was then applied to the less known Pico Alto geothermal area on Terceira Island, Azores. Pico Alto is a promising geothermal field in its early stages of development. Five production wells have been drilled and exploration results presented on maps and cross sections. Here, the existing data were visualised in a 3D model, according to the workflow, in order to gain a better understanding of the Pico Alto geothermal field. The two geological static models presented here provide a useful basis for further research and model workflow applications. Samþáttun og samantekt gagna og rannsókna af jarðhitasvæðum er oft á tíðum flókið ferli. Þrívíð líkangerð er mjög gagnleg við slíka vinnu, auðveldar samanburð og samtúlkun og dregur um leið úr óvissu þegar kemur að staðsetningu jarðhitaholna. Í þessu verkefni er útbúið þrívítt jarðfræðilíkan af jarðhitasvæði sem hefur lengi verið í vinnslu. Jarðhitasvæðið í ...